1992
DOI: 10.1056/nejm199208203270802
|View full text |Cite|
|
Sign up to set email alerts
|

Nitric Oxide Synthase Activity in Infantile Hypertrophic Pyloric Stenosis

Abstract: We suggest that a lack of nitric oxide synthase in pyloric tissue is responsible for pylorospasm in infantile hypertrophic pyloric stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
112
0
12

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 328 publications
(127 citation statements)
references
References 26 publications
3
112
0
12
Order By: Relevance
“…Taken together, these results suggest an undersupply of the thickened pyloric smooth muscle with NO in IHPS patients. Because nNOS is expressed in the human enteric nervous system but not in enteric smooth muscle cells (9,30), the reduced abundance of nNOS mRNA transcripts normalized against ubiquitous housekeeping genes most likely reflects hypertrophy and hyperplasia of enteric smooth muscle cells leading to a relative decrease of enteric neurons in tissue specimen of IHPS patients when compared with controls. Therefore, expression of nNOS mRNA was assessed further by normalization against PGP9.5, a marker for general neural tissue (Fig.…”
Section: Quantitative Expression Patterns Of Nnos First-exon Mrna Varmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these results suggest an undersupply of the thickened pyloric smooth muscle with NO in IHPS patients. Because nNOS is expressed in the human enteric nervous system but not in enteric smooth muscle cells (9,30), the reduced abundance of nNOS mRNA transcripts normalized against ubiquitous housekeeping genes most likely reflects hypertrophy and hyperplasia of enteric smooth muscle cells leading to a relative decrease of enteric neurons in tissue specimen of IHPS patients when compared with controls. Therefore, expression of nNOS mRNA was assessed further by normalization against PGP9.5, a marker for general neural tissue (Fig.…”
Section: Quantitative Expression Patterns Of Nnos First-exon Mrna Varmentioning
confidence: 99%
“…Recent evidence suggested a reduced expression of neuronal nitric oxide synthase (nNOS) in IHPS, because the pyloric circular muscle layer shows decreased staining of nNOS-positive neurons (9) and decreased expression of nNOS mRNA normalized against GAPDH (10). Additionally, genetic-linkage analysis suggests the nNOS gene as a susceptibility locus for hereditary IHPS (11).…”
mentioning
confidence: 99%
“…Non-adrenergic, noncholinergic (NANC) innervation to the pylorus is predominantly inhibitory and mediates relaxation of the sphincter (Anuras et al 1974). A high density of NOSimmunopositive nerve cells and fibres has been demonstrated in the pylorus (Ekblad et al 1994), and significant reduction of NOS activity of the pylorus has been demonstrated in infantile hypertrophic pyloric stenosis (Vanderwinden et al 1992). It has been shown that transgenic mice with homozygous depletion of the nNOS gene develop grossly enlarged stomachs with hypertrophy of the pyloric sphincter (Huang et al 1993).…”
mentioning
confidence: 99%
“…Les poissons du nord de l'Atlantique, incluant les limandes (flets), les éperlans, les harengs, les lycodes, les chaboisseaux et les morues, fabriquent des PAG ainsi que des glycoprotéines antigel de cinq types différents, qui sont non homologues et remarquablement diverses en terme de séquence et de structure [1]. Les limandes plie rouge (Pleuronectes americanus) fabriquent une PAG découverte il y a plus de 30 ans [2]. Cette PAG (de «type I ») est composée d'une simple hélice α amphipatique de 33 acides aminés [3] qui se lie à la face pyramidale de la glace [4] via une surface riche en résidus alanine et complé-mentaire de celle du réseau cristallin de la glace.…”
Section: Pourquoi Les Limandes Vivant Dans L'atlantique Nord Ne Gèlenunclassified